2010
DOI: 10.1021/ja109044r
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lantipeptides in Escherichia coli

Abstract: Lantipeptides are ribosomally synthesized and posttranslationally modified peptides containing thioether cross-links. We describe the preparation of seven different lantipeptides in Escherichia coli and demonstrate that this methodology can be used to incorporate nonproteinogenic amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
206
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(214 citation statements)
references
References 17 publications
4
206
2
2
Order By: Relevance
“…The successful production of nisin in E. coli was achieved by coexpression of hexahistidine-tagged NisA (His 6 -NisA) and untagged NisB from a pRSFDuet-1 vector and untagged NisC from a pACYC vector (21). For the purpose of in vitro studies on NisB, these constructs were altered such that the gene for a hexahistidinetagged NisB (His 6 -NisB) was cloned into the multiple cloning site 1 (MCS-1) of pRSFDUET-1 and the gene for His 6 -tagged precursor peptide NisA was inserted into MCS-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful production of nisin in E. coli was achieved by coexpression of hexahistidine-tagged NisA (His 6 -NisA) and untagged NisB from a pRSFDuet-1 vector and untagged NisC from a pACYC vector (21). For the purpose of in vitro studies on NisB, these constructs were altered such that the gene for a hexahistidinetagged NisB (His 6 -NisB) was cloned into the multiple cloning site 1 (MCS-1) of pRSFDUET-1 and the gene for His 6 -tagged precursor peptide NisA was inserted into MCS-2.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the successful preparation of nisin in Escherichia coli by coexpression of the precursor peptide NisA with NisB and NisC (21). Hence, the NisB protein must be functional in E. coli, prompting renewed attempts at establishing an in vitro reconstituted activity.…”
mentioning
confidence: 99%
“…Our ProcM directionality study focused on one of the substrates, ProcA3.2 (Fig. 6A), which has four Ser/Thr residues but is dehydrated only three times (25,31). HSEE analysis of the onefold and twofold dehydrated ProcA3.2 indicated that ProcM initially dehydrated the third Thr in the core peptide followed by the second Thr (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electrocompetent BL21(DE3) cells were cotransformed with the plasmids. A single colony was picked to inoculate a culture used to overexpress modified GeoAI as described for other lantibiotics (28). The cells were lysed, and modified GeoAI was purified using nickel affinity chromatography and reversed phase (RP) HPLC (48).…”
Section: Methodsmentioning
confidence: 99%